Preparation of Si quantum dots by phase transition with controlled annealing - Fang, Liyuan; Tang, Libin; Teng, Kar Seng; Xiang, Jinzhong (Nanotechnology, 2021)
Silicon quantum dots (Si-QDs) are excellent luminescent material due to its unique optoelectronic properties and have huge application potential in the field of photodetection. Recently, there has been much research interests in developing low-cost, facile and environmentally friendly methods to prepare the nanomaterials in addition to yielding excellent performances. In this article, we developed a novel preparation method of producing Si-QDs film based on carbon-silicon composite. The film was synthesized by co-sputtering using magnetron sputtering technique and studied at different annealing temperatures. Upon annealing, the film was transformed from an amorphous state to a crystalline state leading to Si-QDs precipitation, which can be observed at a low temperature of 600 °C. A Si-QDs thin film/n-Si photodetector was then prepared and characterized. The device exhibited a high specific detection rate (D*) of 1.246 × 1012cm Hz1/2W-1under 940 nm (1.1 mW cm-2) infrared radiation at 5 V bias. It also demonstrated good responsiveness and stability.Silicon quantum dots (Si-QDs) are excellent luminescent material due to its unique optoelectronic properties and have huge application potential in the field of photodetection. Recently, there has been much research interests in developing low-cost, facile and environmentally friendly methods to prepare the nanomaterials in addition to yielding excellent performances. In this article, we developed a novel preparation method of producing Si-QDs film based on carbon-silicon composite. The film was synthesized by co-sputtering using magnetron sputtering technique and studied at different annealing temperatures. Upon annealing, the film was transformed from an amorphous state to a crystalline state leading to Si-QDs precipitation, which can be observed at a low temperature of 600 °C. A Si-QDs thin film/n-Si photodetector was then prepared and characterized. The device exhibited a high specific detection rate (D*) of 1.246 × 1012cm Hz1/2W-1under 940 nm (1.1 mW cm-2) infrared radiation at 5 V bias. It also demonstrated good responsiveness and stability.